DOS quick reference guide - Mathur , Rajiv ([India] : Galgota pub, 1989)
This book, with more than 200,000 copies in print, has been completely updated to DOS Version 4 with a new section devoted to the DOS shell. Includes explanations of all the DOS, batch, configuration, and Edlin commands. Alphabetized, with numerous examples.